EXOGENOUS APPLICATION OF ALA REGULATES GROWTH AND PHYSIOLOGICAL CHARACTERS OF Leymus chinensis (TRIN.) TZVEL. UNDER LOW TEMPERATURE STRESS - S. A. Anjum; Wang Ran; Niu Jian-hang; Ali Zohaib; Li Jin-huan; Liu Mei-ru; Song Ji-xuan; Lv Jun; Wang San-gen; Zong Xue-feng (Journal of Animal and Plant Sciences, 2016)
A pot experiment was conducted to assess regulation of growth and physiology of Leymus chinensis plants by exogenous application of 5-Aminolevulinic acid (ALA) at various concentrations (10, 50 and 100 mg/L) exposed to low temperature stress. In control distilled water was applied as spray under both normal and low temperature stress. Experiment was laid out using completely randomized design with three replications. Results revealed that low temperature stress impaired plant growth and photosynthetic pigments while elevating the accumulation of malondialdehyde (MDA), osmolytes and enzymatic antioxidants of L. chinensis plants. However, application of ALA improved the plant height, leaf area, plant fresh and dry weight, root activity, chlorophyll a, chlorophyll b and total chlorophyll content of L. chinensis plants when compared with control under low temperature stress. Treatment with ALA at a concentration of 10 and/or 50 mg/L was found better pertaining to growth while 100 mg/L was better regarding biosynthesis of photosynthetic pigments. Furthermore, ALA treatment enhanced the accumulation of soluble proteins, soluble sugars and free proline while reducing the MDA content and 10 and/or 50 mg/L ALA concentration was superior. Application of ALA also boosted the enzymatic antioxidants viz. super oxide  dismutase (SOD), peroxidase (POD), catalase (CAT), ascorbate (APX) and glutathione reductase (GR) as compared to control at low temperature and application of 10 mg/L performed better. It may be concluded that treatment of ALA was helpful in the attainment of tolerance against low temperature stress manifested through improved growth, biosynthesis of photosynthetic pigments, higher levels of osmolytes and antioxidant enzymes, and reduced MDA content of L. chinensis plants.
Keywords: Leymus chinensis; 5-Aminolevulinic acid (ALA); low temperature; growth; osmolytes; antioxidants